Cultural Tourism, Religion and Religious Heritage in Castile and León, Spain - González-González, Miguel (The international journal of religious tourism and pilgrimage, 2022)
Tourism is a driving force of the economy for many countries around the world. The large number of architectural and intangible World Heritage Sites have consolidated those countries in their strong positions as cultural tourism destinations. Within cultural tourism, religious tourism is particularly prominent. This work focuses on Spain and specifically on some of its regions which lack beaches but possess a wealth of religious cultural heritage, such as Castile and León, which have viewed such heritage as an asset to attract a different kind of tourist. The objectives of this study are to highlight the value of religious heritage as a tourist attraction, analyse the potential of religious heritage for religious and non-religious tourism, and observe religious tourism as an asset in depressed areas. The criterion that governs the study is to determine the profile of these tourists and their relationship with the destination. Methodologically, this work is an analysis, assessment and reflection of different processes, practices and events from a social anthropology perspective. The results identify a type of tourist more aware of sustainability and more respectful of the environment and culture, and therefore, more in tune with religion and religious heritage.